’¡Menos Estado y más sociedad civil!’ Una crítica al primado de la dialéctica de comunidades sobre la dialéctica de Estados“ - García Matías, Bettina (Nómadas. Critical Journal of Social and Juridical Science, 2015)
In this article we invite to make a critical reflection on the idea of "civil society" and how this is in conflict with the defense of the State.